2021
DOI: 10.3390/insects12090827
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Core Genes of Toll-like Receptor Pathway from Lymantria dispar and Induced Expression upon Immune Stimulant

Abstract: The gypsy moth, Lymantria dispar, is a polyphagous forest pest worldwide. The baculovirus, Lymantria dispar multiple nucleopolyhedrovirus (LdMNPV) is a natural pathogen of L. dispar. The Toll-like receptors (TLR) pathway plays a crucial role in both innate and adaptive immunity in animals. However, The TLR pathway and its underlying immune mechanism against baculovirus in L. dispar have not been explored. In this study, eleven TLRs and five downstream TLR pathway components were identified and characterized fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(48 reference statements)
1
1
0
Order By: Relevance
“…TLR proteins from the C. tripartitus transcriptome (TLR-2, TLR-6, and TLR-7) may act as membrane receptors to drive the MyD88-dependent pathway of the Toll cascade with assistance from intracellular components. Consistent with our results, core genes of the TLR pathway ( TLRs, MyD88, and kinases) have also been identified in the transcriptome of gypsy moth, Lymantria dispar [ 70 ].…”
Section: Discussionsupporting
confidence: 89%
“…TLR proteins from the C. tripartitus transcriptome (TLR-2, TLR-6, and TLR-7) may act as membrane receptors to drive the MyD88-dependent pathway of the Toll cascade with assistance from intracellular components. Consistent with our results, core genes of the TLR pathway ( TLRs, MyD88, and kinases) have also been identified in the transcriptome of gypsy moth, Lymantria dispar [ 70 ].…”
Section: Discussionsupporting
confidence: 89%
“…Herein, five Toll receptor genes of M. persicae were cloned, which is less than the number of Toll-related genes identified in other insects, ranging from 7 in Acyrthosiphon pisum to 14 in Bombyx mori [ 35 , 36 ]. Sequence analyses indicated that three typical conserved domains of the Toll family were found in five MpToll amino acid sequences, and a similar conservation has been found in Toll sequences in B. mori and Lymantria dispar [ 37 , 38 ]. Different domains may play distinct roles, with the TIR domain being a key site of interaction with intracytoplasmic adaptor protein MyD88 to enable intracellular signaling [ 39 ], while the LRRs domain was thought to be particularly suitable for interactions between proteins [ 40 ].…”
Section: Discussionmentioning
confidence: 71%